The Implementation of Laptop Mobile in the Teaching-Learning Process in Islamic Boarding School - Evi Fatimatur Rusydiyah; Fiena Saadatul Ummah; Ali Mudlofir (TARBIYA: Journal of Education in Muslim Society, 2020)
AbstractComputer literacy has become an interesting issue in the field of education as the integration of technology in education develops rapidly and continues to increase in the future. One aspect of computer literacy teacher’s and student’s perceptions and attitudes to use computers for classroom instruction. Unfortunately, this has been a challenge for incorporating technology during the teaching and learning process. The current study aims to analyze the implementation of the use of a mobile laptop in the class and unfold the student’s attitudes toward using laptops during their learning activities. This research was a survey study that includes interviews, observation and documentation as a data collection technique. The subject of the study is 312 students from seventh to ninth grade. Data analysis was done by the following steps: data collection, data reductions, data analysis, and conclusion making. The study finds that 1) course content and learning activities have been predetermined/ predesigned and stored in the laptops, 2) every student have access to the device with the help of group work. The study also reveals that the attitude of students toward the use of laptops in the classroom process is positive in the sense that they show satisfaction on the use of laptops. They also acknowledge the advantages of the computer for their learning and show high awareness of the importance of keeping the devices maintained and secured.AbstrakSalah satu bidang Tehnologi pembelajara adalah pemanfaatan teknologi informasi sebagai media pembelajaran. Hal tersebut selaras dengan perkembangan abad 4,0.  Kemampuan siswa dalam menggunakan dan memanfaatkan computer (Komputer Literasi) menjadi isu yang menarik saat ini. Komputer literasi menjadi bagian dari teknologi pembelajaran. Tujuan dari penelitian ini untuk menganalisis implementasi penggunaan laptop Mobile dalam aktivitas belajar di kelas dan bagaimana respon siswa dalam penggunaan laptop Mobile di kelas.  Penelitian ini dilakukan dengan survey. Sedangkan metode pengumpulan datanya dilakukan dengan cara wawancara, observasi, dan dokumentasi. Subjek penelitian ini adalah siswa kelas VII, VIII, dan VIII sejumlah 312 anak. Analisis penelitian ini dilakukan dengan cara mengumpulkan data, mereduksi, menganalisis, dan membuat kesimpulan. Hasil penelitian ini menunjukkan bahwa implementasi penggunaan laptop mobile dilakukan saat proses belajar mengajar dilakukan dengan cara 1) semua materi dimasukkan dalam laptop mobile, 2) semua siswa mendapatkan hak akses untuk menggunakannya, dan 3) aktivitas belajar sudah didesain dalam laptop mobile. Sedangkan respon siswa dalam menggunakan mobile laptop menunjukkan 1) tingkat kepuasaan dalam menggunakan laptop mobile, 2) tingkat kemanfaatan dalam menggunakan laptop mobile, dan 3) tingkat tanggungjawab dalam merawat laptop mobile pada angka rerata yang paling tinggi pada lilihan stuju dan sangat setuju. How to Cite: Rusydiyah, E. F., Ummah, F. S., Mudlofir, A.  (2020).   The  Implementation of Laptop Mobile in the Teaching-Learning Process in Islamic Boarding School. TARBIYA: Journal of Education in Muslim Society, 7 (1), 67-77. doi:10.15408/tjems.v7i1.13650.